2022
DOI: 10.1007/s10896-022-00461-y
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Victimization During the COVID-19 Pandemic Among a Global Online Sample of Sexual Minority Men

Abstract: Purpose We aimed to describe the prevalence of IPV victimization, changes of experiencing IPV victimization, and examined factors associated with more severe or frequent IPV victimization since the COVID-19 crisis among a global sample of sexual minority men (SMM). Methods Data were collected between October and November 2020 through a gay social networking (GSN) application. We used multinominal logistic regression to examine correlates of experiencing any IPV during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
1
5
1
Order By: Relevance
“…We found that participants who were homeless or housing insecure were more likely to experience recent violence victimization. This is in line with the existing literature where studies have reported the association between social and economic vulnerabilities and violence victimization ( Hong et al, 2022 ; Walters et al, 2021 ). For example, one study conducted in California also found that men who inject drugs reported being homeless were more likely to experience violent victimization ( Walters et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that participants who were homeless or housing insecure were more likely to experience recent violence victimization. This is in line with the existing literature where studies have reported the association between social and economic vulnerabilities and violence victimization ( Hong et al, 2022 ; Walters et al, 2021 ). For example, one study conducted in California also found that men who inject drugs reported being homeless were more likely to experience violent victimization ( Walters et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar conclusions are drawn in studies that examined depressive symptoms among women who have experienced intimate partner violence (IPV) victimization. Two systematic reviews of the literature found that there is robust evidence supporting the association between IPV victimization and mental health issues such as depression, anxiety, post-traumatic stress disorder, self-harm, and sleep disorders ( Dillon et al, 2013 ; Lagdon et al, 2014 ) and others found such associations among sexual and gender minority population ( Finneran & Stephenson, 2013 ; Hong et al, 2022 ). Violence victimization experience is also frequent among PWUOs.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies showed racial and ethnic aspects as significant predictors of IPV (Hong et al, 2023; Metheney & Stephenson, 2020; Stults et al, 2021). A longitudinal study demonstrated that Hispanic/Latino participants were more likely to perpetrate IPV compared to Black and White participants (Stults et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Among the analyzed studies, seven of them showed sexual risk behavior as one of the main risk factors for IPV (victimization and/or perpetration) among gay men, whether through multiple partners (Duncan et al 2018; Elísio et al, 2018), or because of the presence of multiple regular and casual partners, along with inconsistent condom use with regular and casual partners (Zhu et al, 2021), or because of group sex throughout life (Miltz et al, 2019), or through involvement with more sexual partners and a homosexual support agency (Wei et al, 2020), through drug use during sex (Wei et al, 2021), or through sex work and use of a digital app to find sexual partners (Hong et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation